The Relevance of Zamakhsyari Dhofier and Abdurahman Mas'ud Thoughts in Reforming Pesantren Education in East Java - Achmadin, Balya Ziaulhaq; Kawakip, Akhmad Nurul; Nafis, Muhammad Muntahibun; Barizi, Ahmad; Asrori, Mohammad (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to analyze the relevance of Zamakhsyari Dhofier and Abdurahman Mas'ud's thoughts in the reform of pesantren education in East Java. Using a qualitative method with a document analysis approach, this study explores the contributions of the two figures in formulating an educational paradigm that is responsive to social change and the needs of learners. The main data sources consist of books, articles, and related writings that describe Dhofier and Mas'ud's thoughts on pesantren education reform. The results of the analysis show that Dhofier's thoughts regarding the integration of religious and general knowledge are very relevant in facing modern challenges, according to him by emphasizing the need for a curriculum that not only focuses on religious aspects, but also includes useful general knowledge. Meanwhile, Mas'ud highlights the importance of practical skill development and the use of technology in pesantren education, which enables pesantren to adapt to the evolving needs of society. The findings reveal that the thoughts of these two figures can be used as an important foundation in developing a more effective and relevant curriculum, teaching methods, and pesantren education policies. This research is expected to provide insights for policy makers and education practitioners in implementing sustainable education reform in pesantren. Thus, the thoughts of Dhofier and Mas'ud not only enrich the academic discourse, but also make a real contribution to the development of pesantren education in the modern era.